Sulfation of Agarose from Subantarctic Ahnfeltia Plicata (Ahnfeltiales, Rhodophyta): Studies of Its Antioxidant and Anticoagulant Properties in Vitro and Its Copolymerization with Acrylamide - Encina-Rojas, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Ortiz-Nunez, J (Kluwer Academic Publishers, 2014)
Aqueous extraction of Ahnfeltia plicata collected in the Magellan ecoregion afforded agarose devoid of sulfate groups. This neutral agarose was subjected to sulfation with SO3-pyridine complex, giving an aqueous soluble derivative with 35.5% sulfate groups. Analysis by Fourier transform infrared spectroscopy (FT-IR) and by 1H and 13C NMR spectroscopy indicated that this derivative was sulfated at positions C-6 of the ?-galactopyranosyl residue and C-2 of the ?-3,6-anhydrogalactopyranosyl residue and partially sulfated at position C-2 of the ? residue. The antioxidant capacity of sulfated agarose was evaluated by the oxygen radical absorbance capacity (ORAC) method, ABTS radical cation, hydroxyl radicals, and chelating assays. This capacity of sulfated agarose toward peroxyl radicals was higher than that of commercial ?-carrageenan, while native agarose presented good activity, with an ORAC value similar to that of commercial ?-carrageenan. Sulfated agarose presented good antioxidant capacity toward other radicals. Copolymerization of sulfated agarose with acrylamide was achieved using ceric ammonium nitrate as initiator. NMR spectroscopy indicated grafting of polyacrylamide at position C-4 of ?-galactopyranosyl residues. © 2014, Springer Science+Business Media Dordrecht.